Risk Factors for Early Pancreatic Allograft Thrombosis Following Simultaneous Pancreas-Kidney Transplantation: A Systematic Review. (12th October 2020) - Blundell, Jian; Shahrestani, Sara; Lendzion, Rebecca; Pleass, Henry J.; Hawthorne, Wayne J.
Simultaneous pancreas-kidney (SPK) transplantation remains the most effective treatment for providing consistent and long-term euglycemia in patients having type 1 diabetes with renal failure. Thrombosis of the pancreatic vasculature continues to contribute significantly to early graft failure and loss. We compared the rate of thrombosis to graft loss and systematically reviewed risk factors impacting early thrombosis of the pancreas allograft following SPK transplantation. We searched the MEDLINE, EMBASE, The Cochrane Library, and PREMEDLINE databases for studies reporting thrombosis following pancreas transplantation. Identified publications were screened for inclusion and synthesized into a data extraction sheet. Sixty-three studies satisfied eligibility criteria: 39 cohort studies, 22 conference abstracts, and 2 meta-analyses. Newcastle-Ottawa Scale appraisal of included studies demonstrated cohort studies of low bias risk; 1127 thrombi were identified in 15 936 deceased donor, whole pancreas transplants, conferring a 7.07% overall thrombosis rate. Thrombosis resulted in pancreatic allograft loss in 83.3% of reported cases. This review has established significant associations between donor and recipient characteristics, procurement and preservation methodology, transplantation technique, postoperative management, and increased risk of early thrombosis in the pancreas allograft. Further studies examining the type of organ preservation fluid, prophylactic heparin protocol, and exocrine drainage method and early thrombosis should also be performed.